Casting a Wider Net: A Critique of the Boundaries Imposed by White Privilege in Adult Education - Elaine Manglitz; Lisa Merriweather (Adult Education Research Conference, 2002)
In this paper, we review and critique the literature on white privilege to identify ways the Eurocentric culture undergirds our social practices in adult education. Africentrism, an alternative to Eurocentrism, will be used as an example of how the discourse can be expanded. Finally, we will offer recommendations for the field.